2019
DOI: 10.2147/rmhp.s180359
|View full text |Cite
|
Sign up to set email alerts
|

<p>Open disclosure of adverse events: exploring the implications of service and policy structures on practice</p>

Abstract: PurposeThe aim of this study was to explore the service and policy structures that impact open disclosure (OD) practices in New South Wales (NSW), Australia.Participants and methodsAn explorative study using semi-structured interviews was undertaken with 12 individuals closely involved in the implementation of OD in hospitals at policy or practice levels within the state of NSW, Australia. Interviews explored the service and policy structures surrounding OD and the perceived impact of these on the implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Nurses' perceptions of the proportion of patients being told about errors as soon as they happen and getting an explanation of why the event occurred were also much lower than what was reported by outpatients in previous studies (Bryant et al, 2017;Carey et al, 2019). Although these findings are not directly comparable due to nurses reporting on a global rate of disclosure while patients in the previous study reported on a single event, the findings do align with previous research demonstrating low adherence to open disclosure processes (Finlay et al, 2013;Harrison, Walton, Smith-Merry, Manias, & Iedema, 2019;Walton et al, 2018). While examining patient-reported health care error rates remains an important area of quality assurance and patient-centred care, these rates will likely underestimate error rates in cancer clinics until open disclosure is common practice.…”
Section: Discussionsupporting
confidence: 77%
“…Nurses' perceptions of the proportion of patients being told about errors as soon as they happen and getting an explanation of why the event occurred were also much lower than what was reported by outpatients in previous studies (Bryant et al, 2017;Carey et al, 2019). Although these findings are not directly comparable due to nurses reporting on a global rate of disclosure while patients in the previous study reported on a single event, the findings do align with previous research demonstrating low adherence to open disclosure processes (Finlay et al, 2013;Harrison, Walton, Smith-Merry, Manias, & Iedema, 2019;Walton et al, 2018). While examining patient-reported health care error rates remains an important area of quality assurance and patient-centred care, these rates will likely underestimate error rates in cancer clinics until open disclosure is common practice.…”
Section: Discussionsupporting
confidence: 77%
“…This realist synthesis identifies five initial programme theories highlighting the factors that are required for successful OD in maternity settings from the perspective of three different interest groups (families; clinicians and services). Some of these factors have been previously identified, and are not unusual in studies of OD in general health care [ 10 , 89 96 ] or more recent NHS England policy interventions [ 97 ]. Our realist synthesis adds to this, contributing detailed descriptions of the barriers and facilitators to this work across the entirety of the OD process for different stakeholders.…”
Section: Discussionmentioning
confidence: 98%
“…Some of our included studies [ 6 , 48 , 76 , 78 , 83 ] considered a wider socio-political promise of OD as an ethical practice. As such, it encapsulates an ethos of care and communication with patients and families that includes consideration both of alternative forms of expertise and user entitlement [ 6 , 96 ]. This ethos is challenged in situations of poor outcome [ 76 , 101 ], when resources required to support harmed families and staff are eroded [ 95 ] and when expectations of learning for future improvement evaporate.…”
Section: Discussionmentioning
confidence: 99%
“…This could be through staff establishment of clinical incidents disclosure and an anonymous feedback system between clients, nurses, and the Ministry of Health. The open disclosure and feedback framework is known to improve professional conduct and quality of care in the United States, Australia and United Kingdom (Harrison et al, 2019, Harrison et al, 2017). The community health providers need to work with and sensitize the community, group leaders and parents to accept and encourage youth to participate in activities that reduce HIV transmission.…”
Section: The Implication For Practice and Policymentioning
confidence: 99%